2019
DOI: 10.1088/1742-6596/1321/2/022090
|View full text |Cite
|
Sign up to set email alerts
|

The differences in geometry cognitive learning results using ICTAdobeFlash CS6 program

Abstract: This research is motivated by the lack of students’ interest in learning mathematics that isconsideredto be difficult and tedious. Then, this problem results the low cognitive learning outcomes of the students. The matter happens because the teacher is still considered to be the centre in learning process, the lack of variations in instructional media, and the way the teachers teach in the class. This study aims to determine whether there are differences in the students’ cognitive learning outcomes from the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The 21st century is also characterized by the amount of information that is available anywhere and can be accessed at any time and communication can be done from anywhere (Prastika & Masniladevi, 2021). In line with the opinion of (Zainil et al, 2019) changes in scientific technology that inspire educators to push the boundaries of technology integration in the classroom.…”
Section: Introductionmentioning
confidence: 70%
“…The 21st century is also characterized by the amount of information that is available anywhere and can be accessed at any time and communication can be done from anywhere (Prastika & Masniladevi, 2021). In line with the opinion of (Zainil et al, 2019) changes in scientific technology that inspire educators to push the boundaries of technology integration in the classroom.…”
Section: Introductionmentioning
confidence: 70%
“…At least in two last decades, a lot of empirical studies which focus on the use of ICT-based or -assisted mathematics learning for cultivating numerical literacy have been carried out widely in numerous educational institutions around the world. Some studies revealed that ICT-based or -assisted mathematics learning had significant positive effect on students' numerical literacy [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Nevertheless, some other studies showed that ICT-based or -assisted mathematics learning did not have significant effect on students' numerical literacy [39][40][41][42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…In another case, many studies showed that ICT-based orassisted mathematics learning had moderate positive effect on students' numerical literacy [23,25,29,33,37,39,[61][62][63][64][65][66]. Even, other numerous studies revealed that ICT-based orassisted mathematics learning had strong positive effect on students' numerical literacy [24, 26, 27, 30, 32, 34-36, 38, 52, 67-72].…”
Section: Introductionmentioning
confidence: 99%